Pengembangan Ekonomi Masyarakat Desa Moain Melaui Pembuatan Keripik Daun Bayam - Micael Ririhena; Makdalena Idwata; Diana Mesmory; Elisa Kastera; Marthea Abrahamz; Yosepina Etwiory; Adelia Romsery; Lidya Malwewan; Milya Malwewan; Christy Tetkily; Kristi Talapia; Yandry Porumau (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Moain Village is one of the villages that is a KKN location for Undergraduate Program students in PSDKU, Pattimura University. Based on observations, it is known that around where the people of Moain Village live, there is a lot of empty land (idle land) that can be used to grow spinach. Apart from that, Moain Village is one of the villages producing spinach which is marketed in Tiakur City. Therefore, KKN students took the initiative to improve the economy of the community in Moain village, namely through developing the Spinach Leaf Chips product. This activity of making spinach leaf chips was carried out to provide knowledge about processing spinach leaves and help the economy of the community in Moain village. This activity aims to provide knowledge and understanding to the community in order to improve the local economy by utilizing the land around where they live. The evaluation results show that the program for making spinach leaf chips is able to improve the economy of the local community and has a good impact.